DESIGN OF SPUN PILE FOUNDATION AND ANCHORED DIAPHRAGM WALL FOR A RENTAL OFFICE BUILDING WITH A BIOPHILIC APPROACH IN SURABAYA - Fatarani, Nadira
The leased office with a biophilic design consists of 11 floors with 3 basement floors functioning as parking lots and 8 floors above ground level. This Final Project aims to design a foundation that carries the load of the superstructure and to design a retaining wall for basement excavation construction. The leased office is designed using spun pile foundation with a diameter of 0.6 meters with a pile depth of 11 meters and is tied into a pile group using a pile cap. The lateral bearing capacity of single and group piles is carried out using LPILE and GROUP software. The settlement analysis is also carried out in the form of elastic settlement, consolidation and differential settlement. The basement excavation construction has a total depth of 10.5 meters, so that a retaining wall is designed to maintain the safety of the excavation. The retaining wall used is a diaphragm wall with a wall thickness of 0.8 m and a wall depth of 25 meters, and reinforcement is used in the form of earth anchors installed at an elevation of -3.5 meters and -8 meters. Analysis for the design of retaining walls is carried out with the help of PLAXIS 2D software with a phased construction method.